Smart Goat System Design and Construction in IoT-Based Goat Pens using Nodemcu ESP8266 - Hidayah, Siti Nur; Maulana, Halim (Hanif Journal of Information Systems, 2024)
Modern agriculture requires innovative approaches in farm management to improve efficiency and security. This thesis aims to design a smart goat system in a goat pen equipped with an anti-theft security system will based on the IoT. This system uses a ultrasonic sensor to monitor the condition of the goat's drinking water needs. In addition, it is equipped with anti-theft technology that utilizes magnetic sensors on the cage door to detect people entering around the cage if the system is activated in real-time. The collected data is integrated into the blink server to allow remote monitoring by the farmer. A mobile application was also developed as a UI that makes it easier for farmers to manage and monitor the barn effectively. By combining aspects of smart cages and anti-theft systems, this research aims to provide a comprehensive solution that can enhance farm security and optimize productivity simultaneously. The tool used in this research is Nodemcu ESP8266